FORMULASI SABUN CAIR ANTIBAKTERI EKSTRAK ETANOL 70% DAUN PUTRI MALU (Folium Mimosa Pudica L.) - saharuddin (Yayasan Pendidikan Medika Indonesia, 2021)
Mimosa Pudica plants can be used to treat infectious diseases. This study was to examine the presence of antibacterial activity in mimosa pudica leaf extracts against Escherichia coli and Staphylococcus aureus, to determine differences in antibacterial activity at various concentrations. Antibacterial activity test was carried out by disk diffusion method. Antibacterial activity is characterized by the formation of a clear zone around the paper disk called the inhibitory zone. This study used 4 concentration treatments, namely 1%, 2%, 3% and 4% as well as a formula without concentrated mimosa pudica leaf extract as a negative control and and one of the industrial antibacterial soap products as a positive control. Based on the results of the means using the SPSS application, showed the influence of antibacterial activity on Escherichia coli and Staphylococcus aureus, the concentration of extract extracts of 4% is the concentration of mimosa pudica leaf in inhibiting the growth of Escherichia coli and Staphylococcus aureus. best in forming inhibition zones with an average diameter of 20.53 mm in Escherichia coli and 24.50 mm in Staphylococcus aureus.